Kidney function outcomes following thermal ablation of small renal masses - Raman, Jay D (World J Nephrol, 2016)
The diagnosis of small renal masses (SRMs) continues to increase likely attributable to widespread use of axial cross-sectional imaging. Many of these SRMs present in elderly patients with abnormal baseline renal function. Such patients are at risk for further decline following therapeutic intervention. Renal thermal ablation presents one approach for management of SRMs whereby tumors are treated in situ without need for global renal ischemia. These treatment characteristics contribute to favorable renal function outcomes following kidney tumor ablation particularly in patients with an anatomic or functional solitary renal unit.